Prevention of omalizumab for seasonal allergic rhinoconjunctivitis: a retrospective cohort study - Tang, Rui; Lei, Shubin; Zhu, Liping; Lv, Yuzhen; Li, Hong (Frontiers in Immunology, 2022)
Background: Allergic rhinoconjunctivitis (ARC) is an allergic disease which is characterized by conjunctival and nasal symptoms such as edema and congestion of conjunctiva, rhinorrhea, sneezing and blocked nose. Seasonal ARC (SARC) is usually induced by seasonal allergens and often occur in specific time during the year. Traditional treatment of SARC include nasal corticosteroids, antihistamine, and mast cell membrane stabilizer. Biological agents such as omalizumab has also been proved effective in treatment of SARC. Objectives: We aim to certify the preventative efficacy of omalizumab for SARC and explore its influence factors. Methods: Medical records of 64 SARC patients were retrospectively analyzed, generalized linear models were used to analyze influence factors of efficacy of omalizumab. Results: Compared with forepassed pollen season without omalizumab treatment, the combined symptom and medication score (CSMS) of ARC with pre-seasonal omalizumab was significantly lower (with omalizumab: 0.67[0.00,1.83], without omalizumab: 4.00[2.83,4.96], p<0.001, max score=6). Subgroup analysis was conducted to explore the influence factor of preventative efficacy of omalizumab. The symptom score, medication score and CSMS with omalizumab treatment were not significantly different among different age, gender, dosage, and injection date subgroups (p>0.05). Conclusion: Pre-seasonal omalizumab treatment could significantly relief SARC related symptom and reduce medication use. This preventative efficacy would not be influenced by the dosage and injection times of omalizumab. Single time of 300mg omalizumab could achieve satisfactory outcome.